Immigrants' Language Skills: The Australian Experience in a Longitudinal Survey - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper is concerned with the determinants of English language proficiency (speaking, reading and writing) among immigrants. It presents a model of immigrant destination language acquisition based on economic incentives, exposure to the destination language, and efficiency in second language acquisition. A unique data set, the Longitudinal Survey of Immigrants to Australia, is used to test the model. This survey had three waves, at about 6 months, 18 months and 3? years after immigration. The analyses are performed by wave, type of language skill and gender using probit analysis. Bivariate probit analysis is used across waves. The hypotheses are supported by the data. The bivariate probit analysis indicates a positive correlation in the unexplained component that declines with time between waves, indicating a regression to the mean in English language proficiency.
Keywords: J61; J15; I29; 330; immigrants; language skills; longitudinal survey; Australia; Migranten; Sprache; Einwanderungsrecht; Schätzung; Australien